Cultural Dimension of Rule of Law and Social Episteme - Sangroula, Yubaraj (Kathmandu School of Law Review, 2018)
Rule of Law, despite being subject to wide attention and acceptance without any dispute, has enough ground to be critically analyzed from dimension and dynamism of the cultural practice of every concerned country adhering to the norm. Since social episteme of the country is perfectly and variably unique to each other, no exact notion regarding rule of law can be imported and exported like a business commodity. Thus, this paper, in detail, sheds ideas on difference of rule of law in oriental and occidental jurisprudence. Deeming the harmonious society with stable peace as fi nal outcome of rule of law, this very paper builds an alternatively concrete insight on rule of law that befi ts the change of time and essence of divergent societies.